Implementation of Feminist Counseling Services on Student Behavior in Education - Titik Wiyul Fithri; Zadrian Ardi; Netrawati (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This study was conducted based on the phenomenon aimed at obtaining a picture of discriminatory student behavior. In recent years, cases of discrimination against women and minorities have increased, so that more serious efforts are needed to address this problem. In this article, we will discuss how feminist counseling can help students overcome discriminatory behavior and increase their gender awareness and self-power. The method in this study is qualitative with library research. The results of this study are that the most important foundation for conducting feminist counseling is an understanding of the concept of feminism. Gender awareness is built through a commitment to ending domination, oppression and privilege related to gender issues and gender bias, including racism, class systems, colonialism, heterosexism, ethnocentrism, white supremacy and age issues.